The Culture of Peace in the municipal schools of Ponta Grossa from the perspective of complexity (Olhar de Professor, 2025)
This study investigated the Culture of Peace from the perspective of complexity, aiming to analyze strategies used to promote it in two municipal schools in Ponta Grossa, Brazil. A qualitative, exploratory approach was adopted, based on field research conducted with 43 participants through semi-structured interviews. All interviews were audio-recorded, with participants signing an Informed Consent Form. The theoretical framework was based on the works of Farias and Bicalho (2024), Morin (2011), Nascimento (2021), and Salles Filho (2019). The results show that, although the importance of a Culture of Peace is acknowledged, challenges remain regarding the training of school professionals, practical implementation, and the need for stronger school-family partnerships. Effective strategies require structural changes and a transdisciplinary approach that encourages practices of dialogue, mediation, and peaceful coexistence.
Keywords: Conflicts; School context; Education